In-Vitro Differentiation Adipose-Derived Mesenchymal Stem Cells into Pancreatic Progenitor Cells - Hermina Novida; Agung Pranoto; Askandar Tjokroprawiro; Sony Wibisono; Purwati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Adult stem cells are currently reliable sources of mesenchymal stem cells for regenerativetherapy, include diabetes mellitus. The aim of this study is to develop endocrine pancreatic progenitor cellscharacterized by Pdx1 and insulin expression from rat adipose-derived mesenchymal stem cells using twosteps in-vitro differentiation.Methods: In this experimental study, ADMSCs were isolated from rat adipose tissue and exposed toinsulinogenic differentiation medium containing nicotinamide, activin A and glucagon-like peptide-1 (GLP1). After induction, the existence of pancreatic progenitor cells (PPCs) was confirmed by immune-stainingassay of Pdx1 and insulin.Results: After three weeks of in-vitro differentiation, expression of Pdx1 and insulin proteins showed upas green in the immunofluorescence assay. Immunofluorescence intensity of Pdx1 was higher in PPCs thanin ADMSCs control (p<0.05). Immunofluorescence intensity of insulin was also higher in PPCs than inADMSCs control (p<0.05). Therefore, in-vitro differentiation was successful to develop PPCs from ratADMSCsConclusion: This study has demonstrated the in-vitro differentiation of ADMSCs into PPCs that expressedPdx1 and insulin